2020
DOI: 10.3390/nano10071374
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Responses of Human Lymphatic Endothelial Cells to Carbon Nanomaterials

Abstract: One of the greatest challenges to overcome in the pursuit of the medical application of carbon nanomaterials (CNMs) is safety. Particularly, when considering the use of CNMs in drug delivery systems (DDSs), evaluation of safety at the accumulation site is an essential step. In this study, we evaluated the toxicity of carbon nanohorns (CNHs), which are potential DDSs, using human lymph node endothelial cells that have been reported to accumulate CNMs, as a comparison to fibrous, multi-walled carbon nanotubes (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…Moreover, Cu, N‐doped CDs and CB NPs at the same mass concentrations induced comparable cytotoxicity (Figure 4). Previous studies compared carbon nanotubes and CB NPs and showed that CB NPs were more biocompatible to endothelial cells compared with carbon nanotubes (Long, Xiao, Liu, & Cao, 2017; Sano et al, 2020). Therefore, we suggested that the cytotoxicity of Cu, N‐doped CDs to HUVECs was only modest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cu, N‐doped CDs and CB NPs at the same mass concentrations induced comparable cytotoxicity (Figure 4). Previous studies compared carbon nanotubes and CB NPs and showed that CB NPs were more biocompatible to endothelial cells compared with carbon nanotubes (Long, Xiao, Liu, & Cao, 2017; Sano et al, 2020). Therefore, we suggested that the cytotoxicity of Cu, N‐doped CDs to HUVECs was only modest.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Although carbon-based conductive materials can be degraded through enzymatic oxidation using horseradish peroxidase, or hydrolytically through lipases, 164,165 the complete degradation and fate of CNTs and graphene-based materials in the body are still relatively unknown. However, in vitro and in vivo studies have shown that a variety of cell types such as macrophages, [166][167][168] endothelial cells, 169 pulmonary epithelia, 170,171 intestinal epithelia 172 and neuronal cells 173 can degrade and take up carbon-based conductive materials. Therefore, understanding how carbon-based conductive materials in bone scaffolds are processed and degraded by the specialized cell types they will interact with will be important for establishing safety in clinical translation.…”
Section: Cellular Processing Mechanisms Of Carbon-based Conductive Ma...mentioning
confidence: 99%
“…Since nanocarbons are allotropic to carbon black, they can be easily compared on a mass-based basis; indeed, a significant number of papers have already used carbon black as negative controls. [51,52,[97][98][99][100][101][102][103][104][105][106] Unfortunately, positive controls have not yet been identified for nanocarbons, although the use of ISOspecified positive controls for chemicals can be acceptable to ensure that the experimental system is functioning.…”
Section: Appropriate Controlsmentioning
confidence: 99%